The Influence of Religious Attitudes in Turkish Muslim on Women's Hijab Fashion Style and the Role of Reference Groups - Serhat Ata; Abdulvahap Baydaş; Şule Say (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2022)
The practice of hijab fashion gains new meanings. Along with fashion, hijab is beyond religious and political meaning and appears as an object of consumption in Turkey. The effect on the purchasing decision process in Turkey may vary according to the family structure the role and status in the society and the environment of consumers. The convenience sampling method was used in the selection of 448 people to participate in the study. In the research, the survey technique, one of the quantitative research methods, was chosen as the data collection method. This paper has examined to determine the effect of religious attitudes of women wearing hijab on the choice of hijab fashion, type of purchase behavior and the moderating role of reference groups. Within the result of the study, when the relationship between the religious attitude, hijab fashion style and purchasing behavior is examined, it is found that internalized belief dimension affects religion-based purchase, planned purchase, and hijab fashion style. Significant relationships were found between the dimension of traditional religiousness, types of purchase, and hijab fashion style. Traditional religiousness affects, religion-based purchase socialized purchasing behavior, brand-based purchase, and hijab fashion style. When the relationship between dependent and independent variables are examined by participating in the moderating role of the reference groups, it is seen that family, friends and role models play moderating role in this relationship.